PEMANFAATAN LIMBAH SERAT TALI BENESER DALAM MENINGKATKAN KUAT TEKAN DAN KUAT TARIK BELAH BETON - Afifah Agnia; Kusno Adi Sambowo; Sittati Musalamah (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2021)
This study aims to determine the utilization of fiber rope waste (strapping band) in increasing the compressive strength and tensile strength of concrete with fiber cross-section size of 2-3 mm and length of 60 mm with variations in the addition of 0 kg/m3, 0,25 kg/m3, 0,5 kg/m3, 0,75 kg/m3, and 1 kg/m3 concrete .the compressive strength of the plan is 30 MPa. The specimen is cylindrical size 150 mm x 300 mm with concrete making planning refers to SNI 03-2834-2000. The results with the addition of rope fibers (strapping band) shows the compressive strength of variations 0 kg/m3, 0,25 kg/m3, 0,5 kg/m3, 0,75 kg/m3, and 1 kg/m3 respectively are 12,55 MPa, 8,87 MPa, 16,608 MPa, 11,418 MPa and 12,644 MPa with the optimum value of concrete compressive strength of 16,608 MPa at variations of the addition of 0,5 kg/m3of fibers. Thus from all the compressive strength values obtained, there are no concretes that reaches the compressive strength of the plan. Whereas the results of tensile strength test are 1,42 MPa, 0,8 MPa, 1,35 MPa, 1,06 MPa and 1,13 MPa respectively with the optimum tensile strength value of 1,53 MPa in variations of addition of 0,5 kg/m3 fibers.